Das intervenções internacionais à responsabilidade de proteger: análise das justificativas políticas, morais e jurídicas dadas às operações bélicas para proteção dos direitos humanos - Souza, Wendell Carlos Guedes de (2016)
The wars fought for humanitarian purposes carry itself a controversial aspect because they represent, during its course, the expense of their own human rights. Around that contrast, intense discussions gain prominence about the justifications given for the promotion of armed interventions, aimed at protection of human rights, against sovereign states which become genocides stage and ethnic cleansing campaigns against their populations, almost by default of internal control mechanisms. Indeed, humanitarian activism that took shape in the 1990s brought to light new settings to the traditional model of intervention, especially in relation to the perception of peace enforcement in light of the Responsibility to Protect doctrine. From the indifference of world leaders with the civil war in Somalia to the aerial bombardment of the Western powers against the genocide in Kosovo – operation this, it is worth mentioning, articulated without authorization of the UN Security Council – emerges the following question: are there reasons really admitted political, moral and legally legitimizing a duty intrusion of the international community in the domestic affairs of States, to put an end to systematic humanitarian crises? This is actually a contentious issue involving points still no consensus that unsettle the opinions of internationalists, such as the universality of human rights, the need to resize the sovereignty and effectiveness of prohibitory rule of war. Taking into account the relevance of these topics, this paper aims, bibliographically, expose and analyze some of the main reasons attributed to such bellicose interventions, highlighting its political, moral and legal aspects (capitulated in that order). From the research of the most commonly alleged justifications for intervenors up to the present day, it is intended to better contribute to the formation of a critical sense about the claim of just causes of war in the future.